Nanoparticles for antiparasitic drug delivery - Yuzhu Sun; Dongmei Chen; Yuanhu Pan; Wei Qu; Haihong Hao; Xu Wang; Zhenli Liu; Shuyu Xie (Taylor & Francis Group, 2019)
As an emerging novel drug carrier, nanoparticles provide a promising way for effective treatment of parasitic diseases by overcoming the shortcomings of low bioavailability, poor cellular permeability, nonspecific distribution and rapid elimination of antiparasitic drugs from the body. In recent years, some kinds of ideal nanocarriers have been developed for antiparasitic drug delivery. In this review, the progress of the enhanced antiparasitic effects of different nanoparticles payload and their influencing factors were firstly summarized. Secondly, the transport and disposition process in the body were reviewed. Finally, the challenges and prospects of nanoparticles for antiparasitic drug delivery were proposed. This review will help scholars to understand the development trend of nanoparticles in the treatment of parasitic diseases and explore strategies in the development of more efficient nanocarriers to overcome the difficulty in the treatment of parasite infections in the future.